Smell, Taste and Tangibility of the Sacred (some examples from the religious practice in Croatia) - Belaj, Marijana (2006)
The basis of this work is the worshipping of patron saints. In people?s minds, patron saints can merely exist as a fact or they can be the object of a truly fervent belief. The latter, which will be the focus of my work, implies one?s dedicated participation in devotion ? an active dialogue with the sacred, the sensation of the sacred. I will observe this sensation of the sacred, this religious experience, through the prism of the senses harnessed in its shaping. The work is based on the fragments of the research conducted into people?s belief in patron saints on the territory of Croatia. It relies, to a lesser degree, on the data contained in manuscript collections and published collections and, to a higher degree, on field research. Expressions of devotion to patron saints are many and varied, but for this occasion I have singled out those which clearly outline the intertwinement of the concrete and the abstract, in other words, those which indicate the wish to discover the true behind the sensory and at the same time, to concretize the unfathomable in a figure accessible to the senses. In the same context, through the prism of the senses, I will demonstrate the process of sacralization of a place which is otherwise, by virtue of its provenance, marked as absolutely non-religious, even anti-religious. The sacralization of this place is revealed in the unrestrained experiences and interpretations of the participants in a celebration, experiences and interpretations which, by their meaning, undoubtedly fall into the domain of the religious.